Legal Analysis of Cracking Down on Violations of Notary Code of Ethics According to Law No. 2 of 2014 concerning Amendments to the Notary Position Law - Avianti, Grace; Putri, Dinda Arista; Franciska, Maria; Edward, Kent (CV. Rayyan Dwi Bharata, 2023)
Notary is closely related to agrarian or land law. The notary also has the authority regarding the making of land deeds. Notary as a profession, of course, also has a code of ethics in the profession. The Notary Code of Ethics is a moral principle determined by the association of Indonesian Notary Associations based on the congress decision of the association / or determined and regulated in the laws and regulations governing this matter which apply to, and must be obeyed by each and all members of the association and all persons who carry out the duties and positions of a Notary. Regarding the code of ethics of the notary profession, it is contained in the Law on Notary Positions. This research will discuss the application of the Law on Notary Office (UUJN) in the prosecution of violations of the Notary's code of ethics. An example of the application of UUJN is in the case in Kudus where a Notary who issued a Sale and Purchase Deed was fraudulent in a house transaction. The types of sanctions that will be applied to the above cases are contained in Article 85 UUJN which can be categorized into types of administrative sanctions, namely temporary dismissal; honorable discharge and dishonorable discharge from office.